The Shift to a Cashless Society in Cebu City: User Behavior and Implications for the Cash Management Sector - Espiriti, Lynneth; Polinar, Mark Anthony N.; Delantar, Alexander Franco A. (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The global shift toward a digital economy is accelerating the adoption of cashless systems. However, infrastructural, social, and economic barriers create uneven adoption, especially in developing regions. This transition presents both opportunities and challenges for financial inclusion and the cash management sector. A quantitative survey of 533 respondents examined digital payment habits, comfort levels, and acceptance of a cashless economy. Using binomial logistic regression and Kruskal-Wallis tests, the study analyzed how age, gender, employment, usage frequency, and comfort affect support for going fully digital. Results showed younger respondents and high-frequency users were significantly more supportive. Gender, employment, and comfort were not significant predictors. However, group-level differences in comfort and usage across age and employment categories highlight the persistent influence of socioeconomic factors on digital engagement. While digital payments are frequently used for online shopping, retail, and transit, concerns remain about privacy, inequality, and internet reliability. The key finding is that regular use of digital tools more than demographics or stated preference drives acceptance. This necessitates that the cash management sector modernizes operations, invest in digital capabilities, and build inclusive infrastructure to remain relevant. The study offers critical guidance for policymakers and industry leaders navigating the cashless transition.